পিতৃস্মৃতি পিতৃকথা : কিংবদন্তি বনফুল - মুখোপাধ্যায়, অসীম কুমার, ১৯৩৩- (কলকাতা : একুশ শতক, 2011)
Memoirs of the author about his father Banaphula, 1899-1979, Bengali author from West Bengal, India.
Donated By Akbar Ali Khan
In Bengali.
Keywords: Banaphula, -- 1899-1979.; Mukhapadhya, Ashim Kumar, -- 1933-; Authors, Bengali -- Biography; Bengali literature